jcde 2020
DOI: 10.37421/jcde.2020.10.344
|View full text |Cite
|
Sign up to set email alerts
|

Cement Soil Stabilization as an Improvement Technique for Rail Track Subgrade, and Highway Subbase and Base Courses: A Review

Abstract: This research paper summarizes published research works on the suitability of cement as an effective chemical stabilizer to improve the strength and durability requirements of sand to be used as subgrade and base courses for rail track and road construction respectively. Advantages and problems associated with soil stabilization using chemicals have also been briefly discussed in this report. It has been confirmed that ordinary Portland cement is an effective chemical stabilizer to improve both the index and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…The implication is that unlike in the case of cement, by increasing the proportion of HCWPAN, lightweight composites are produced. Solihu [56] and Srivastava et al [57] in their research work observed similar effects on density when using cement for soil stabilization.…”
Section: Resultsmentioning
confidence: 64%
“…The implication is that unlike in the case of cement, by increasing the proportion of HCWPAN, lightweight composites are produced. Solihu [56] and Srivastava et al [57] in their research work observed similar effects on density when using cement for soil stabilization.…”
Section: Resultsmentioning
confidence: 64%
“…Different researchers found numerous optimum cement content for the stabilization of expansive soil. According to Solihu [25], 14 % cement is the optimum cement content for silty clay soil. Based on the suitability of sub-grade soils, the studied soils were classified under Poor and not allowed to use for sub-grade materials.…”
Section: Estimation Of Optimum Cement Contentmentioning
confidence: 99%
“…Also, water can infiltrate the pavement through cracks that reflect light through the surfacing. Another problem is that the stabilizing reaction is reversible if CO2 has access to the material, and the layer's strength can be reduced [20]. When we add 8% cement to soil, cohesion increases by 37% while the UCS increases by 76% [21,22].…”
Section: Introductionmentioning
confidence: 99%